OPTIMIZATION OF COFFEE PEEL (CASCARA) DRYING PROCESS CONDITIONS ON COLOR CHARACTERISTICS USING RESPONSE SURFACE MEHTHODOLOGY - Asri Widyasanti; Shintya Devita Maharani (Jurnal Teknologi dan Industri Pertanian Indonesia, 2025)
Coffee peel, a by-product of coffee beverage production, is an underutilized resource despite its potential health benefits, particularly its antioxidant content. This by-product can be repurposed as a raw material for cascara, a drink made from dried coffee peel. The aim of this research is to determine the optimal drying conditions for cascara production and to analyze the effect of varying temperature and drying time using a food dehydrator on the color parameters L*, a*, and b* of the dried coffee peel. The experimental design includes temperature settings of 40C, 50C, and 60C, and drying durations of 2, 3, and 4 hours. The study employed an experimental approach with optimization using the response surface methodology (RSM) based on a central composite design (CCD), utilizing the Design Expert 13 software. The optimum drying condition for Arabica coffee peel was found to be 60C for 2 hours, resulting in an L* value of 29.36, an a* value of 10.96, and a b* value of 17.30, respectively.